BOBS: an Intel 8085 processor simulator - Sousa, Antônio Drumond Cota de; Diniz, Mateus Henrique Medeiros; Puddo, Davi Ferreira; Freitas, Henrique Cota de (Anais da Escola Regional de Alto Desempenho da Região Sudeste (ERAD-SE); 2025: Anais da X Escola Regional de Alto Desempenho da Região SudesteDO - 10.5753/eradse.2025.16918, 2025)
To aid in computer architecture education, this paper introduces a new Intel 8085 processor simulator built in the Rust programming language. The project’s primary motivation is to leverage a new accumulator-based simulator to compose a set of educational tools based on different architectures. Our simulator offers a high-delity emulation of the 8085 architecture, featuring both a terminal and a graphical user interface to cater to diverse learning styles. It includes an integrated assembler and powerful debugging capabilities, most notably a time-travel function that allows users to step both forwards and backwards through their program’s execution. The result is a modern, cross-platform, and open-source simulator designed to provide a comprehensive and safe environment for learning low-level computing concepts.